MET inhibition overcomes radiation resistance of glioblastoma stem‐like cells. Issue 5 (4th April 2016) - De Bacco, Francesca; D'Ambrosio, Antonio; Casanova, Elena; Orzan, Francesca; Neggia, Roberta; Albano, Raffaella; Verginelli, Federica; Cominelli, Manuela; Poliani, Pietro L; Luraghi, Paolo; Reato, Gigliola; Pellegatta, Serena; et al.
Abstract: Glioblastoma (GBM) contains stem‐like cells (GSCs) known to be resistant to ionizing radiation and thus responsible for therapeutic failure and rapidly lethal tumor recurrence. It is known that GSC radioresistance relies on efficient activation of the DNA damage response, but the mechanisms linking this response with the stem status are still unclear. Here, we show that the MET receptor kinase, a functional marker of GSCs, is specifically expressed in a subset of radioresistant GSCs and overexpressed in human GBM recurring after radiotherapy. We elucidate that MET promotes GSC radioresistance through a novel mechanism, relying on AKT activity and leading to (i) sustained activation of Aurora kinase A, ATM kinase, and the downstream effectors of DNA repair, and (ii) phosphorylation and cytoplasmic retention of p21, which is associated with anti‐apoptotic functions. We show that MET pharmacological inhibition causes DNA damage accumulation in irradiated GSCs and their depletion in vitro and in GBMs generated by GSC xenotransplantation. Preclinical evidence is thus provided that MET inhibitors can radiosensitize tumors and convert GSC‐positive selection, induced by radiotherapy, into GSC eradication. Synopsis: GBM radioresistance relies on the inherent properties of its stem‐like cell population (GSCs). MET, which encodes for the HGF receptor, is shown to be a functional marker of GSC radioresistance and a therapeutic target for GSC radiosensitization. MET expression identifies radioresistant GSCs derived from a subset of patients and propagated as neurospheres. In GBMs recurring after radiotherapy, MET expression is more frequent, as compared with matched primary tumors (85% versus 45%). MET drives positive selection of irradiated GSCs, by promoting the DNA damage response via AKT, which sustains ATM activation, and p21 phosphorylation and cytoplasmic retention. When combined with radiotherapy, MET inhibition impairs the GSC DNA damage response and converts GSC selection from positive to negative. Abstract : GBM radioresistance relies on the inherent properties of its stem‐like cell population (GSCs). MET, which encodes for the HGF receptor, is shown to be a functional marker of GSC radioresistance and a therapeutic target for GSC radiosensitization.